Analysis of Demand Volume, Material Supply, and Work Hours against Delta Power Listrindo CV Production Performance - Rozi, Yudi Fakhrul; Aslami, Nuri; Dharma, Budi (Penerbit Goodwood, 2024)
Purpose: Purpose of this research is to find out what factors affect the production performance of CV Delta Power Listrindo so that later it can solve the challenges that exist in its production performance. Methods:. Production performance can be measured through various indicators, such as product efficiency, product quality, production time, and costs incurred. To achieve optimal production performance, companies need to implement various strategies and conduct analysis to find out what factors affect their production performance. CV Delta Power Listrindo finds challenges in its production performance, which requires a more in-depth analysis to find out what factors affect its production performance, this is what motivates researchers to conduct this research. Results: The results of the study describe, the number of requests is positive and significant on production performance, found in the t column section, the variable number of requests has a t value (2.337)> t table (1.703) and a significant 0.028 <0.05. Limitations: Of course, this research has limitations, namely as follows, this research only focuses on certain manufacturing industries, so the results in this study cannot be extended to all industrial sectors, and the data used in this study comes from a certain period of time, so it cannot capture long-term fluctuations that may affect production performance. Contribution : Based on the findings and results of research that shows the number of requests is positive and significant to production performance, variable demand is positive and significant to operational performance, and working hours are positive and significant to production performance. It is hoped that CV Delta Power Listrindo will pay more attention to the amount of demand, material inventory and working hours because these three factors have a positive and significant value on production performance. And it is hoped that further research can examine various factors, in order to find out what factors can affect the production performance of CV Delta Power Listrindo besides demand factors, material inventory, and working hours.